France : 2009 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for France. (IMF Staff Country Reports; Country Report, 2009)
This 2009 Article IV Consultation highlights that the global financial crisis and the contraction of world trade have pulled the French economy into a severe recession and put its financial sector under strain. Structural features combined with early policy action have helped soften the downturn. Executive Directors have noted that the near-term economic outlook remains challenging, with GDP growth expected to decrease by 3 percent in 2009. Directors have also stressed that safeguarding medium-term fiscal sustainability and avoiding unsustainable debt dynamics is a key priority for the coming years.